Neurologic and MRI Abnormalities in Acute Disseminated Encephalomyelitis and Response to Plasmapheresis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The relation between the clinical course and MRI findings and response to plasmapheresis were determined by a retrospective record review of 13 children with acute disseminated encephalomyelitis (ADEM) admitted to St Christopher's Hospital for Children, Philadelphia, PA, during 1998-2003.